Oxy-imino saccharidic derivatives as a new structural class of aldose reductase inhibitors endowed with anti-oxidant activity - Felicia D'Andrea; Stefania Sartini; Ilaria Piano; Matteo Franceschi; Luca Quattrini; Lorenzo Guazzelli; Lidia Ciccone; Elisabetta Orlandini; Claudia Gargini; Concettina La Motta; Susanna Nencetti (Taylor & Francis Group, 2020)
Aldose reductase is a key enzyme in the development of long term diabetic complications and its inhibition represents a viable therapeutic solution for people affected by these pathologies. Therefore, the search for effective aldose reductase inhibitors is a timely and pressing challenge. Herein we describe the access to a novel class of oxyimino derivatives, obtained by reaction of a 1,5-dicarbonyl substrate with O-(arylmethyl)hydroxylamines. The synthesised compounds proved to be active against the target enzyme. The best performing inhibitor, compound (Z)-8, proved also to reduce both cell death and the apoptotic process when tested in an in vitro model of diabetic retinopathy made of photoreceptor-like 661w cell line exposed to high-glucose medium, counteracting oxidative stress triggered by hyperglycaemic conditions.